2016
DOI: 10.1080/1343943x.2016.1229571
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and physiological traits of seeds and seedlings in two rice cultivars with contrasting early vigor

Abstract: Key laboratory of crop cultivation and Farming System, Guangxi university, nanning, P.r. china ABSTRACT Early vigor is important for crop establishment in rice. This study was conducted to determine the seed and seedling traits in relation to early vigor in rice. Laboratory tests and pot experiments were carried out in 2013 and 2014. Morphological and physiological traits of seeds and seedlings were compared between two contrasting rice cultivars, Yuxiangyouzhan with superior early vigor and Huanghuazhan with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…The increased photosynthetic rate is mainly attributed, here, to increased LNC, which in turn might be related to higher SLW. This result is consistent with a previous outdoor pot experiment, where the increased leaf photosynthetic rate of rice cultivar Yuxiangyouzhan (25 days after sowing, compared to that of HHZ) was accompanied with higher leaf soluble protein level and higher SLW 85 , although there are also reports showing strong early vigor might result from a lower SLW, which means larger leaf area with the same leaf weight 30,71,86 .…”
Section: Discussionsupporting
confidence: 92%
“…The increased photosynthetic rate is mainly attributed, here, to increased LNC, which in turn might be related to higher SLW. This result is consistent with a previous outdoor pot experiment, where the increased leaf photosynthetic rate of rice cultivar Yuxiangyouzhan (25 days after sowing, compared to that of HHZ) was accompanied with higher leaf soluble protein level and higher SLW 85 , although there are also reports showing strong early vigor might result from a lower SLW, which means larger leaf area with the same leaf weight 30,71,86 .…”
Section: Discussionsupporting
confidence: 92%
“…Seed weight and seed nutrient content affect plant growth at seedling stage 6 , 7 . Previous studies show a close relationship between seed size or weight and early vigor in rice 3 , 8 . In general, rice seed with thin hull and large embryo are desirable for seed vigor 8 .…”
Section: Introductionmentioning
confidence: 79%
“…Previous studies show a close relationship between seed size or weight and early vigor in rice 3 , 8 . In general, rice seed with thin hull and large embryo are desirable for seed vigor 8 . Seed weight was correlated with plant growth at low P supply up to the flowering stage in soybean, and the effect of seed weight at low P conditions was larger than that at high P conditions 6 .…”
Section: Introductionmentioning
confidence: 79%
“…High seed vigor is aligned with potential of increasing growth and productivity agricultural productivity. Seed weight and seed nutrient content gives impact to plant growth at seedling period [46,47]. Earlier studies done to showed a close relationship between seed size or seed weight and early vigor in rice which reveals that rice seed with thin hull and large embryo are preferable for seed vigor [48].…”
Section: Effect Of Salinity On Seed Vigormentioning
confidence: 99%